Objective measures of writing quality - Kyle, Kristopher, author; Flahive, Douglas, advisor; Berry, Nancy, committee member; Thayer, Marilyn, committee member (Colorado State University. Libraries, 2011)
This study explores the use of objective measures to assess writing quality. Coh-Metrix 2.0, an online text analysis tool, was used to measure 54 linguistic properties of argumentative essays written by English as a Second Language (ESL) and English as a Foreign Language (EFL) students. Using discriminant function analysis, this study found that two models of three objective-measure predictors each were able to significantly discriminate between holistically evaluated high and low quality essays written by ESL students. Two different models of three objective-measure predictors were also able to significantly discriminate between high and low quality EFL essays. These models could not, however, significantly discriminate between high and low quality essays across educational settings. The predictors used in each successful model support the idea that essays containing complex language are generally perceived to be of high quality. The results of this study question, however, the idea that coherent texts have more cohesive textual features, at least in the ESL setting. Furthermore, this study highlights the differences between ESL and EFL writing, though these differences may prove to be related to factors other than educational setting due to some limitations of this study.
Keywords: Coh-Metrix; writing; objective measures; ESL; EFL